The Role of Cash Waqf Linked Sukuk based on Mudarabah Contract (Trustee-Partnership) as MSME Capital Solution - Humaidi, Muchtim; Syamsuri, Syamsuri; Khoirunnisa, Farah (El-Barka, 2023)
This study tries to present a capital solution for MSMEs through the Cash Waqf Linked Sukuk instrument with a mudharabah contract. When viewed from Mandiri Institute data in June 2021 regarding the causes of MSMEs closing their businesses, the main factor was caused by business capital problems with the highest percentage of respondents, namely 45%. Based on these problems, waqf is considered the best mechanism for funding MSME projects. Moreover, waqf has been growing and giving birth to new innovations, namely the Cash Waqf Linked Sukuk (CWLS) program. It can be seen from the increase in the SW-001 series CWLS product with the use of investment returns that have succeeded in providing recovery to the BMM and SME programs by providing capital financing to 100 MSMEs. The method used in this research is descriptive qualitative with a library research approach. The data taken is secondary data in the form of readings sourced from books, magazines, or other sources from various literatures. This study found that cash waqf sukuk based on mudharabah contracts are not the same as mudharabah schemes in general. To solve the MSME capital problem, it is recommended to use the waqf link mudharabah model which can be carried out by synergizing between Islamic microfinance institutions that work together with social institutions or successful Muslim entrepreneurs/entrepreneurs. This social agency acts as a gathering place for MSMEs that need capital as well as a facilitator and supervisor to provide business training and assistance, including aspects of management and fiqh muamalah maaliyah.